Algorithms for Clustering Fuzzy Soft Sets Based on Their Energies - Stojanovic, Nenad; Sezgin, Aslıhan (Soft Computing Fusion with Applications, 2025)
In this paper, we continue the study of fuzzy soft sets and their applications. Besides the significance of energy and $λ$-energy of fuzzy soft sets for developing decision-making algorithms, these energies are also crucial for forming data clustering algorithms. The main result of this work is the development of data clustering algorithms based on the energies of fuzzy soft sets.